Assessment of Radioactive Gaseous Effluent Released From Nuclear Power Plant Ninh Thuan 1 under Scenario of Ines-Level 5 Nuclear Accident - Khai, Nguyen Tuan; Cuong, Le Dinh; Anh, Do Xuan; Thang, Duong Duc; Giap, Trinh Van; Ha, Nguyen Thi Thu; Bac, Vuong Thu; Quang, Nguyen Hao (Communications in Physics, 2015)
Based on guides RG 1.109, RG 1.111 published by United States Nuclear Regulatory Commission (USNRC)~our~research~concentrates on assessing radiation doses caused by radioactive substances released from the nuclear power plant (NPP) Ninh Thuan 1 to the environment under scenario of an INES-level 5 nuclear accident caused by two incidents of the station black out (SBO) and loss of coolant accident (LOCA) using software~RASCAL4.3~provided by the Emergency Operations Center of USNRC. The plant Ninh Thuan 1 is assumed to use the VVER-1200 technology with a total power of 2400 MW\(_{e}\). The input data for the model calculations is based on building the accident scenario, the technical parameters of VVER-1200 technology and the meteorology. The meteorological data on dry and rainy seasons, which are typical for the Ninh Thuan region was also considered. The \(X/Q\) (s/m\(^{3}\)) quality and the maximum dose values were calculated within an area of 40 km radius from the NPP site, where \(X/Q\) (s/m\(^{3}\)) is the ratio of activity concentration to release rate. Based on the obtained results on dose distribution the necessary measures for nuclear emergency preparedness have been proposed according to the IAEA recommendations.